1998
DOI: 10.1095/biolreprod58.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Distribution and Regulation of Aromatase Gene Expression in the Rat Brain1

Abstract: Recent evidence suggests that two cytochrome P450 aromatase (P450arom) mRNA transcripts are present in the rat brain. One of these contains the entire 5'-coding sequence and correlates with the presence of functional enzyme. We designed a new 255-base pair P450arom probe (AROM255) that recognizes only this full-length P450arom mRNA. Ribonuclease protection assays verified that the cRNA probe synthesized from this construct recognized a single RNA species in brain tissues that express aromatase activity, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
84
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 40 publications
17
84
2
Order By: Relevance
“…The sex differences in the volume of these structures that have been observed in these species are influenced by the endocrine state of the subjects in adulthood and do not simply reflect organizational effects of steroids as is the case for volumetric sex differences in the more restricted parts of these nuclei identified as the SDN-POA in rat of the SDA pars compacta in gerbils (see above). The fact that the rat MPN and the quail POM are specifically labeled by a dense expression of aromatase (identified by in situ hybridization in rat and by in situ hybridization and immunocytochemistry in quail) further support this hypothesized homology [13,70,119,147]. Based on this criterion, the sheep sexually dimorphic nucleus of the mPOA would also be homologous [127].…”
Section: The Preoptic Neuronal Circuit Controlling Male Sexual Behavimentioning
confidence: 80%
“…The sex differences in the volume of these structures that have been observed in these species are influenced by the endocrine state of the subjects in adulthood and do not simply reflect organizational effects of steroids as is the case for volumetric sex differences in the more restricted parts of these nuclei identified as the SDN-POA in rat of the SDA pars compacta in gerbils (see above). The fact that the rat MPN and the quail POM are specifically labeled by a dense expression of aromatase (identified by in situ hybridization in rat and by in situ hybridization and immunocytochemistry in quail) further support this hypothesized homology [13,70,119,147]. Based on this criterion, the sheep sexually dimorphic nucleus of the mPOA would also be homologous [127].…”
Section: The Preoptic Neuronal Circuit Controlling Male Sexual Behavimentioning
confidence: 80%
“…However, the ability of estrogens and androgens to work in tandem to regulate male behavior was confirmed by investigators who demonstrated that co-treatment of castrated male animals with estradiol and dihydrotestosterone restored all parameters of male sexual behavior comparable to that of animals treated with testosterone alone (Baum and Vreeburg, 1973). Several brain regions important for controlling male sexual behavior contain aromatase activity (Naftolin, 1975, Selmanoff, 1977, Roselli et al, 1998 providing support for the concept that testosterone can be converted locally to estradiol within selective brain sites. Recent studies using the aromatase null mouse model (ArKO) underscore the importance of brain aromatase and estrogen in male rodent sexual behavior.…”
Section: Introductionmentioning
confidence: 90%
“…Aromat ase is a key enzyme for the production of sex steroids and catalyzes the final step of the biosynthetic pathway of estrogens. Aromatase has been reported to be widely distributed in extragonadal and gonadal tissues including the ovaries (1), testis (2), placenta (3), adipose tissues (4), skin (5), and brain (6). Aromatase is well known to take part in various important functions, such as cell proliferation and differentiation, through estrogen biosynthesis in an endocrine, autocrine, or paracrine fashion (7).…”
mentioning
confidence: 99%